Statistical Study of Cancer in Diyala Provenance - Hasoon Mohammad , Salam; A Salman , Ruaa (Diyala Journal of Medicine, 2022)
Background: Malignant neoplasms are a group of illnesses involving altered cell proliferation with the ability to invade or metastasize to other sites of the body. Not all neoplasms are malignant; benign neoplasms do not metastasize to other parts of the body. Objective: To To find out and subcategorize different types of malignant neoplasms in the Diyala and find the relationship with different criteria, including age, sex, grade….,etc. Patients and Methods: In order to conduct this retrospective study, 158 patients with malignant neoplasmas were chosen from the pathology laboratories spread throughout Provenance-Baquba City between February 2012 and December 2016. For all cases, we do statistical analysis for age, gender, tissue affected, type of surgery, kind of malignant neoplasm, grade, stage, and history of diagnosis and find the relationship of each of these factors with each other. Results: The highest kind of malignant neoplasm within the study was mammary carcinoma, which comprised 39 (24.9%); then dermal malignant neoplasm was 30 (18.9%); and malignant lymphoma was 12 (7.8%); the rest of the other 76 are other malignant neoplasms (48.4%). Conclusion: Mammary carcinoma is the most common malignant neoplasm in the Diyala Region (25 %), followed by dermal carcinoma (19%), and malignant lymphoma (8 %). Age (51–60 years) is a risk factor for malignant neoplasms in the Diyala Region.